Quality Management of Internal Supply Chain in Halal Food Manufacturer - Hartini Ahmad; Rohafiz Sabar; Zulkifli Mohamed Udin; Mohd Faizal Abd Latif; Nizamuddin Zainuddin (International Journal of Supply Chain Management, 2019)
This paper investigates the relationship between the internal supply chain quality management and company performance. The quality management of the internal supply chain is the evergreen research theme in the Halal business process. The research methods utilized the case study approach and collect in-depth information on a single case study. The paper answers the relationship between internal supply chain quality management and the performance of a company. The themes emerged are in terms of the quality control and quality assurance, and technological advent of the internal supply chain. The relationships of the themes identified the business process management and operational excellence as crucial for meeting customers’ demand and expectations. The recommendations for increasing the company performance, besides the quality, are speed, efficiency, flexibility, and capacity.